KLASIFIKASI MINAT BELI PELANGGAN TERHADAP UDANG VANAME MENGGUNAKAN ALGORITMA NAÏVE BAYES - aqillah Aqillah Fadia Haya; Reynaldi Azhar; Muhamad Khandava Mulyadien; Betha Nurina Sari (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Vannamei shrimp is a type of shrimp that is immune to disease attacks and has promising profit opportunities so that many shrimp farming entrepreneurs like this type of vaname shrimp. From 2007 to 2009 Indonesia was able to export this type of vaname shrimp with a total amount of 548,250 tons. The large number of exports has resulted in this shrimp entrepreneur being overwhelmed in overcoming the sales strategy. So this study will have the aim of analyzing whether the classification method with the Naive Bayes algorithm is good enough in overcoming problems in the sales process in one of the ponds on the island of Nusakambangan. The results of this study provide an accuracy value of 83% and a precision value of 0.79%.